Need Analysis of Flipped Learning English-Based Speaking Materials for Faculty Economics and Business Students - Chusna, Sumti; Mukminatien, Nur; Laksmi, Ekaning Dewanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Today's workplace requires workers to master English speaking skills. Preparing the students to communicate in the future workplace; English speaking materials must be well designed and developed. Need Assessment is the vital step to develop a learning material. This research focuses on mapping out the student's needs in the Foreign Language for Specific Course (FLSP) speaking class at the Faculty of Economic and Business, in one of a private university in Malang, Indonesia. This research contributes as a basis to develop speaking materials which aims at providing adequate materials fit to the industrial need. This study uses a qualitative research method which aims at obtaining complete and comprehensive data. Questionnaires and interview were employed to collect the data from 131 students, 2 lectures, and 3 professional business workers. The finding shows the student's English proficiency level ranging from A1 to BI CEFR level, case study as the teaching method, performance-based assessment as the assessment method, the suggested business topic materials, and the evaluation of the existing class.